Survival rate of pulpectomy in primary teeth using Feapex® paste: a clinical study in infants - Abanto, Jenny; Olegário, Isabel; Mendes, Fausto; Bönecker, Marcelo; Corrêa, Maria Salete (Brazilian Dental Science, 2021)
Objective: The aim of this clinical study was to evaluate the survival rate of a new pulpectomy protocol using2% chlorhexidine digluconate gel and Feapex paste for endodontic treatment in primary teeth. Material andMethods: A total of 105 pulpectomies were performed in anterior and posterior teeth of 48 infants (1-3 yearsold) with high caries experience with irreversible pulpitis or pulp necrosis. All treatments were performed bydental surgeons with no specialization in Pediatric Dentistry, under local anesthesia and rubberdam isolation.Manual files were used in conjunction with 2% chlorherixidine gel for root canal instrumentation, and Feapex®paste was used as a obturation material. The clinical and radiographic outcomes were collected by one trainedindependent evaluator with a follow-up period of 24months. Success was determined by the absence of pain,pathological mobility, pathologic bone rarefaction, pathological root resorption and soft tissue pathology aroundthe affected tooth Survival of the endodontic treatment was evaluated by estimating survival rates throughKaplan-Meier curves. Cox Regression analysis with shared fragility were performed to evaluate the associationbetween the independent variables to endodontic treatment failure (alpha=5%). Results: After 24 months, thetreatment survival was 86% (SE=0.03). Root resorption at baseline was associated with a higher risk of failure(HR=2.81; CI=1.12-7.08; p=0.027). The survival rate of the endodontic treated teeth due to dental traumawas 100%, while teeth with dental caries had lower survival rate (85.05%; p0.05). Conclusion: The new protocol using2% chlorhexidine digluconate and Feapex® presented a high survival rate and can be considered as a suitableprotocol for pulpectomy in primary teeth.Trial Registration: REBEC (RBR-282s2f).KEYWORDSRoot canal treatment; Primary teeth; Infants; Pulpectomy.